From Evidence to Clinical Guidelines in Antibiotic Treatment in Acute Otitis Media in Children - Elena Lia Spoială; Gabriela Dumitrita Stanciu; Veronica Bild; Daniela Carmen Ababei; Cristina Gavrilovici (MDPI AG, 2021)
Acute otitis media (AOM) in children represents a public health concern, being one of the leading causes of health care visits and antibiotic prescriptions worldwide. The overall aim of this paper is to unravel the major current insights into the antibiotic treatment of AOM in children. Our approach is three-fold: 1. a preclinical evaluation of antibiotics in animal models of AOM stressing on the advantages of different species when testing for different schemes of antibiotics; 2. an overview on the new antimicrobial agents whose efficacy has been demonstrated in refractory cases of AOM in children; and 3. an analysis of the different guidelines stressing on the differences and similarities between the various schemes of antibiotic treatment. The preferred therapeutic agents remain amoxicillin and the amoxicillin-clavulanate combination for AOM caused by Streptococcus pneumoniae, whereas oral cephalosporin is preferred in AOM due to Moraxella catarrhalis and Haemophilus influenzae. As for the second and third line antimicrobial treatments, there is a wide variety of suggested antibiotic classes with variations in duration and posology. The decision to prescribe antimicrobial treatment as a first-line choice is based on the severity of the symptoms in 16 of the guidelines included in this review.